First-principle investigation on the thermoelectric properties of XCoGe (X = V, Nb, and Ta) half-Heusler compounds. (15th March 2022) - Xiong, Xilin; Wan, Rundong; Zhang, Zhengfu; Lei, Ying; Tian, Guocai
Abstract: Half-Heusler compound is a promising thermoelectric material due to its excellent conversion performance. In this study, we investigate the electronic structure, and thermoelectric properties of XCoGe (X = V, Nb, and Ta) compounds based on density functional theory. Combining the semi-classical Boltzmann transport equation and the deformation potential theory, the thermoelectric properties such as Seebeck coefficient, relaxation time, electrical conductivity, power factor, electronic thermal conductivity, and lattice thermal conductivity are analyzed. The NbCoGe compound possesses a large dimensionless figure of merit, which is related to the large electrical conductivity, small effective mass, and large relaxation time. The ZT values of n- and p-type NbCoGe compounds reach 1.6 and 1.3 at T = 1200 K, respectively. These findings will provide valuable guidance for exploring half-Heusler compounds with high thermoelectric performance.